2003
DOI: 10.1046/j.1365-3091.2003.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution and source of arsenic, copper, tin and zinc within the surface sediments of the Fal Estuary, Cornwall, UK

Abstract: Estuarine sediments commonly form major sinks for contaminants released during industrial activity. Many industrial processes lead to the release of metals initially in solution, which can then be adsorbed on to, for example, Fe hydroxides or clay minerals. However, in the mining industry, there are two major contaminant waste streams: (1) metals discharged in solution via mine drainage; and (2) particulate grains of the ore-forming or related minerals released after ore processing. The release of particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Previous authors (Hughes, 1999;Pirrie et al, 1997Pirrie et al, , 2002Pirrie et al, , 2003 reported the presence of As, Cu, Hg, Pb and Zn in estuarine areas of Falmouth and Fowey due to mining activities. Sediments from estuaries of the Thames, Stour and Orwell also present significant enrichments of Cd, Cu, Hg, Pb and Zn (Wright and Mason, 1999).…”
Section: Enrichment Factor (Ef) Assessmentmentioning
confidence: 97%
“…Previous authors (Hughes, 1999;Pirrie et al, 1997Pirrie et al, , 2002Pirrie et al, , 2003 reported the presence of As, Cu, Hg, Pb and Zn in estuarine areas of Falmouth and Fowey due to mining activities. Sediments from estuaries of the Thames, Stour and Orwell also present significant enrichments of Cd, Cu, Hg, Pb and Zn (Wright and Mason, 1999).…”
Section: Enrichment Factor (Ef) Assessmentmentioning
confidence: 97%
“…Many river basins in the world are seriously affected by heavy metals released into the environment from mining and industrial activities as shown by Wolfenden and Lewin [43]; Swennen et al [44]; Hursthouse et al [45]; Hudson-Edwards et al [46]; and Pirrie et al [47]. Polluted particles are transported and deposited into the floodplains and wetlands, which act as a temporary sink for heavy metal deposition and storage in river basins [48].…”
Section: Active Stream Sedimentsmentioning
confidence: 99%
“…Although originally developed for mineral exploration, actual river sediment reconnaissance surveys have subsequently been found to be of great value for highlighting geochemical anomalies, as well as for showing the regional patterns of nearby soils [54]. Spread of contaminants can occur along rivers which drain industrial areas as shown by Wolfenden and Lewin [43], HudsonEdwards et al [46], Hursthouse et al [45,55], Pirrie et al [47] and Sullivan and Taylor [56]. Moreover sediments become enriched with many heavy metals due to continuous deposition of suspended particles from the overlying water [57], or by dust particles [29].…”
Section: Active Stream Sedimentsmentioning
confidence: 99%
“…Spread of contaminants can occur along rivers which drain the industrial areas as shown by Wolfenden and Lewin [24], Hudson-Edwards et al [25], Hursthouse et al [26], Pirrie et al [27]. The sediments become enriched with many heavy metals due to continuous deposition of suspended particles from the overlaying water [28], or by dust particles [29].…”
Section: Actual River Sedimentsmentioning
confidence: 99%